2017
DOI: 10.1093/ijnp/pyx087
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Changes Associated with Intermittent Explosive Disorder: A Gene-Based Functional Enrichment Analysis

Abstract: BackgroundIntermittent explosive disorder is defined as a recurrent, problematic, and impulsive aggression that affects 3% to 4% of the US population. While behavioral genetic studies report a substantial degree of genetic influence on aggression and impulsivity, epigenetic mechanisms underlying aggression and intermittent explosive disorder are not well known.MethodsThe sample included 44 subjects (22 with a DSM-5 diagnosis of intermittent explosive disorder and 22 comparable subjects without intermittent exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…One of these was “hormone metabolic processes,” with several high‐ranking DMPs annotated to thyroid hormone pathway genes ( TRH, FDX1, TNX2, and TXNRD2 ), consistent with prior evidence of thyroid hormone dysregulation in pathological aggression in humans (Evrensel, Ünsalver, & Özşahin, ) and attack behavior in mice (Hrabovszky et al, ). Another set of enriched pathways related to inflammatory processes, including “cytokine secretion.” This is in line with reported alterations in DNAm and expression levels of cytokine genes in individuals with a chronic history of childhood physical aggression (Provençal, Suderman, Caramaschi, et al, ; Provencal, Suderman, Vitaro, Szyf, & Tremblay, ), as well as in individuals diagnosed with IED (Montalvo‐Ortiz et al, ). We also identified enrichment for multiple CNS‐related processes, such as “Axon guidance.” Interestingly, this same GO pathway was found to be highly enriched in the EWAS study on global aggression by van Dongen et al () as well as a recent bioinformatic analysis combining findings from six GWAS studies on aggression‐related phenotypes (Fernàndez‐Castillo & Cormand, ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of these was “hormone metabolic processes,” with several high‐ranking DMPs annotated to thyroid hormone pathway genes ( TRH, FDX1, TNX2, and TXNRD2 ), consistent with prior evidence of thyroid hormone dysregulation in pathological aggression in humans (Evrensel, Ünsalver, & Özşahin, ) and attack behavior in mice (Hrabovszky et al, ). Another set of enriched pathways related to inflammatory processes, including “cytokine secretion.” This is in line with reported alterations in DNAm and expression levels of cytokine genes in individuals with a chronic history of childhood physical aggression (Provençal, Suderman, Caramaschi, et al, ; Provencal, Suderman, Vitaro, Szyf, & Tremblay, ), as well as in individuals diagnosed with IED (Montalvo‐Ortiz et al, ). We also identified enrichment for multiple CNS‐related processes, such as “Axon guidance.” Interestingly, this same GO pathway was found to be highly enriched in the EWAS study on global aggression by van Dongen et al () as well as a recent bioinformatic analysis combining findings from six GWAS studies on aggression‐related phenotypes (Fernàndez‐Castillo & Cormand, ).…”
Section: Discussionsupporting
confidence: 84%
“…However, a gene ontology analysis identified significant enrichment for genes involved in a range of central nervous system processes. As would be expected for brain‐based phenotypes, epigenetic alterations in genes involved in neural function have also been observed in psychiatric disorders that feature aggression as a diagnostic criterion, such as childhood disruptive behavior disorders (Barker et al, ; Cecil et al, ), IED (Montalvo‐Ortiz, Zhang, Chen, Liu, & Coccaro, ), and ASPD (Beach, Brody, Todorov, Gunter, & Philibert, ; Checknita et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Puhalla et al showed that IED, aggression frequency, AUD, and childhood abuse were all independently associated with overall aggression; however, only individuals with IED displayed increased intoxicated aggression related to the degree of AUD severity [7]. Therefore, genetic vulnerability could be one possible neurobiological basis for this type of behavior [8]. For example, a history of childhood abuse could enhance the frequency of engaging in overall aggression and developing IED, which may increase the association between SUD severity and well-known intoxicated aggression.…”
Section: Substance Use Disorder (Sud) and Intermittent Explosive Diso...mentioning
confidence: 99%